2005
DOI: 10.1177/1087057105276034
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages of the Ussing Chamber in Drug Absorption Studies

Abstract: By adding high concentrations of test drugs to an Ussing chamber with rat jejunum, we established a system that yields very high correlations between the rat absorption percentage and the membrane permeability, and that can accurately predict the absorption percentage for rats. An advantage of this technique is that, unlike the results obtained using Caco-2, the slope of the absorption/membrane-permeability curve is gentle, which facilitates a more exact prediction of the absorption percentage. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…The equipment is commercially available but custom made equipment is also used. The amount of tissue necessary for one set-up ranges from 3.8 mm 2 [125] -5 mm 2 [126] in the smaller version, to 0.65-1.78 cm 2 in the larger version [104,123,[127][128][129]. The smallest chambers (mm 2 -range) have, up to now, only been used for absorption studies [125,126] and are very promising in the light of the scarce availability of human tissue.…”
Section: Ussing Chambermentioning
confidence: 97%
See 2 more Smart Citations
“…The equipment is commercially available but custom made equipment is also used. The amount of tissue necessary for one set-up ranges from 3.8 mm 2 [125] -5 mm 2 [126] in the smaller version, to 0.65-1.78 cm 2 in the larger version [104,123,[127][128][129]. The smallest chambers (mm 2 -range) have, up to now, only been used for absorption studies [125,126] and are very promising in the light of the scarce availability of human tissue.…”
Section: Ussing Chambermentioning
confidence: 97%
“…The chambers have been successfully used up to 90 min [130], 120 min [123,129], 180 min [19,84,104] and even to 8 h as reported by Lampen et al [131] who showed that the conductivity remains constant up to 8 h [131]. Polentarutti et al have validated their Ussing chamber preparations thoroughly and based on the potential difference (PD) (> 4mV small intestine; > 6mV colon), short circuit current (SCC), resistance, permeability for propranolol and mannitol as well as morphological evaluation they have concluded that tissue integrity is maintained up to 180 min [104].…”
Section: Ussing Chambermentioning
confidence: 99%
See 1 more Smart Citation
“…The tacrolimus across the rat intestinal membrane was studied with the Ussing diffusion chamber (24). Sprague Dawley rats, weighing 280-350 g, were fasted overnight and then anesthetized with sodium pentobarbital (30 mg/kg).…”
Section: Transport Of Tacrolimus Across the Intestinal Membrane Via Amentioning
confidence: 99%
“…31,32) Compared to other in vivo and in situ methods, this technique is relatively simple and enables quantifying the intestinal membrane , respectively. These three parameters are comparable to those of Caco-2, suggesting that Caco-2 is suitable for an in vitro system to examine the permeation of zinc.…”
Section: )mentioning
confidence: 99%